Developing Vocabulary Acquisition through Effective Listening and Appropriate Note Taking - OUAZETA, Amel (Journal of Human Sciences, 2016)
Vocabulary is a basic element in any language, for that students use some tools to help them in learning vocabulary, like checking in dictionaries, asking teachers or peers and learning from word lists. In the current article, we shed some light on students’ attitudes and performances on some types of texts. In our study, we noticed that from the exposure to some texts read to students, they listen and take notes at the same time. After listening and taking notes, students write new essays based on the notes taken. From this practice, students also get used to the combination between modules and to benefit from the information they get in classes. In this case, it is the combination between the Oral Expression and the Written Expression module. At the end of the experiment, we noticed that teacher’s verbal language and body language helped students to develop their listening comprehension, way of taking notes, their system of abbreviations and symbols and theycould benefit from taking notes to learn new words.